Effects of 200 ppb added chromium from chromium propionate on the growth performance and carcass characteristics of finishing pigs - Bergstrom, J.R.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,207 pigs (PIC 337 × 1050) were used in a 103-d experiment in a commercial research barn to evaluate the growth performance and carcass characteristics of finishing pigs fed 200 ppb chromium propionate. There were 22 replicate pens per treatment with 25 to 28 pigs per pen for the evaluation of chromium propionate from d 0 to 84 and 11 replicates per treatment for evaluating chromium propionate (0 and 200 ppb) and Paylean (0 and 9 g/ton) in a split-plot arrangement from d 84 to 103. Pigs were weighed (avg. 67.7 lb) and randomly allotted to 2 corn-soybean meal-based dietary treatments, a control diet and the control diet with 200 ppb chromium from chromium propionate. The treatments were fed through three 4-wk dietary phases (d 0 to 28, d 28 to 56, and d 56 to 84). On d 84, pigs fed the control or chromium treatment were allotted to a fourth dietary phase containing either 0 or 9 g/ton Paylean, resulting in a split-plot design. For the overall period (d 0 to 84), growth performance of pigs fed the control or 200 ppb chromium propionate was not different. From d 84 to 103 and overall (d 0 to 103), pigs fed diets containing Paylean had increased (P < 0.01) ADG and final weight. However, a chromium propionate × Paylean interaction (P < 0.04) was observed for ADFI and F/G from d 84 to 103 and overall (d 0 to 103) F/G. The reason for the interaction was that the magnitude of response to Paylean was slightly greater in pigs fed the control than in pigs fed chromium. Regardless, the F/G of pigs fed Paylean was considerably better (P < 0.01) from d 84 to 103 (2.43 vs. 2.89) and overall (d 0 to 103, 2.50 vs. 2.56) than that of those not fed Paylean. Carcass data from 500 of the pigs were available for comparison of carcass characteristics. Pigs fed Paylean had greater (P < 0.05) plant live weight than pigs not fed Paylean. Chromium propionate did not influence any of the carcass characteristics measured. This experiment provides further evidence that Paylean improves late-finishing growth performance. In this trial, growing and finishing pigs did not respond to the dietary inclusion of chromium from chromium propionate.
Keywords: Chromium; Lysine; Ractopamine HCl